Microcrédito e microempreendedor: o caso do Crediamigo na região do Vale do Jequitinhonha Minas Gerais - Leandro Martins Vieira (2015)
Microcredit has awakened the interest of rulers and scholars from all over the world due to its supposed capacity to fight poverty and create economic development opportunities in areas traditionally less-favored economically. This interest increased even more when Muhammad Yunus, founder of the Grameen Bank, was awarded the Nobel Peace Prize in 2006. In Brazil, several policies toward productive microcredit have been intensified since the late 1990s, highlighting the Crediamigo from Banco do Nordeste. Since then, a number of national and international studies have sought to understand the dimension of the phenomenon of microfinance and its impact on improving the living conditions of the borrowers and the financial sustainability of microfinance institutions. However, little has been studied about the microenterprises that utilize this type of financing. This paper seeks to clarify how microcredit influences the promotion of entrepreneurship in Vale do Jequitinhonha. The choice of this location was motivated by the low social indicators in the region, making it one of the poorest and least developed regions in Brazil, and because of the high number of women who are the heads of their households and their low level of education, which make them prime targets for the use of microcredit based on the methodologies usually associated with this type of loans. In order to explain this phenomenon, a study was conducted based on mixed methods with concomitant triangulation, where the first quantitative research was consisted of a survey of 182 micro-entrepreneurs who used microcredit and were attended by Crediamigo. The collected data was grouped by means of cluster analysis, aiming to find similarities among micro-entrepreneurs. The qualitative research was done through a case study where the semi-structured interviews were conducted by means of content analysis. It was made, from the collected data, a socioeconomic profile of the entrepreneurs belonging to each one of the four groups found, as well as the classification of the types of businesses aiming at the application of the resources gotten in microfinance. The data analysis made it possible to verify that microcredit has a positive influence on the profitability and cash flow origination in businesses once they enable entrepreneurs to buy merchandising, to accumulate inputs, and to originate floating stock in better conditions than they used to have before. However, the same listing was not found in employment generation, since a big part of it is composed of individual workers.